Time Spent Gaming and Social Competence in Children: Reciprocal Effects Across Childhood. Issue 3 (23rd April 2019) - Hygen, Beate W.; Belsky, Jay; Stenseng, Frode; Skalicka, Vera; Kvande, Marianne N.; Zahl‐Thanem, Tonje; Wichstrøm, Lars
Abstract : Electronic games are popular and many children spend much time on this activity. Here we investigate whether the quantity of time children spend on gaming is related to their social development, making this the first study to examine this relationship in children. We examine prospective relations between time spent gaming and social competence in a community sample of Norwegian 6 year olds ( n  = 873) followed up at ages 8, 10, and 12, controlling for socioeconomic status, body mass index, and time spent gaming together with friends. Results revealed that greater social competence at both 8 and 10 years predicted less gaming 2 years later and that more age‐10 gaming predicted less social competence at age 12 but only among girls.